Assistência clínica do cão neonato em sepse: a importância na sobrevivência - Raffi, Maria Clara Boni (Universidade Estadual Paulista (Unesp), 2022)
Two thirds of neonatal deaths are related to bacterial infections, and newborns dogs are more susceptible to develop sepsis until three weeks of life. The main agents isolated, in these cases, are Escherichia coli, Streptococcus sp., Staphylococcus pseudointermedius, Staphylococcus aureus, Pseudomonas sp., Klebsiella spp., Enterobacter sp., Proteus spp., Salmonella spp. The maternal and neonatal risk factors include dystocia, improper use of antibiotics in parturients, low quality of mother’s milk or mastitis; prematurity, hypothermia, poor gain weight and lacks in environmental management. Neonates in sepsis can evolve acutely, appearing subclinical infections or unspecified ones, like hypothermia, hyperthermia, dehydration, weight loss, absence or weak sucking reflex, diarrhea, abnormal vocalization and cyanotic mucous. Due to the mechanism of precarious thermoregulation and immaturity of the organ systems at birth, there is a constant need of maternal contact and clinical assistance, so these newborns grow up as they are supposed to. Newborn assessment, through Apgar score; temperature monitoring; evaluation of suckle, rooting and righting reflexes, can rate puppies’ viability. Neonates in sepsis are in need of immediate therapeutic care, like fluid, oxygen and warming therapy; exams; systemic antibiotics, which should be initiated empirically with amoxicillin/clavulanic acid or cephalosporins, because of the requirement of emergency treatment, and after that according to the result of culture and antibiogram.

Dois terços das mortes neonatais correlacionam-se a infecções bacterianas, sendo os cães recém-nascidos são preponderantemente mais susceptíveis a desenvolver sepse nas três primeiras semanas de vida. Os principais agentes isolados, nesses casos, são Escherichia coli, Streptococcus sp., Staphylococcus pseudointermedius, Staphylococcus aureus, Pseudomonas sp., Klebsiella spp., Enterobacter sp., Proteus spp., Salmonella spp. Os fatores de risco materno e neonatais englobam a distocia, uso indevido de antibióticos nas parturientes, leite materno de baixa qualidade ou com mastite; prematuridade, hipotermia, baixo ganho de peso e falhas no manejo ambiental. Neonatos em sepse podem evoluir de maneira hiperaguda, com infecção subclínica, ou apresentarem sinais clínicos inespecíficos, como hipotermia, hipertermia, desidratação, perda de peso, reflexo de sucção ausente ou diminuído, diarreia, vocalização anormal, e mucosas cianóticas. Devido ao mecanismo de termorregulação precário e imaturidade dos seus sistemas orgânicos ao nascimento, há necessidade constante do contato materno-neonatal e de assistência clínica, para que esses recém-nascidos cresçam a termo. A avaliação clínica neonatal, através do escore de Apgar; temperatura; reflexos de sucção, postura e endireitamento, possibilita avaliar a vitalidade do filhote. Os neonatos em sepse carecem de suporte terapêutico imediato, como fluidoterapia, oxigênio e aquecimento; coleta de exames e uso de antibioticoterapia sistêmica, inicialmente empírica, com amoxicilina com ácido clavulânico ou cefalosporinas de terceira geração, devido à necessidade do tratamento emergencial, e em seguida consoante o resultado de cultura e antibiograma
Clinical assistance of the canine neonate in sepsis: importance in survival
Keywords: Canine sepsis; Mortality; Bacterial infecctions; Neonatal care; Veterinary assistance; Sepse canina; Mortalidade; Infecções bacterianas; Manejo neonatal; Assistência veterinária